THE DECREASE IN THE LEVEL OF CORROSION HAZARD IN THE RATIONAL DESIGN OF METAL STRUCTURES - Gibalenko, O. M. (Science and Transport Progress, 2016)
Purpose. The paper highlights development the principles of robust (sustainable) design in the constructive decisions substantiation of the primary and secondary protection for steel structures based on the control of corrosion risk level of construction projects, structural adaptation, and technological rationality when operating in conditions of corrosive environments impact. Methodology. The computational methods for assessing the reliability and structural safety were used and developed by authors. In the base of methods there is a construction of information-analytical databases attributive parameters on the corrosion state of metal construction for the improvement and control measures the primary and secondary corrosion protection. Findings. The basis was proposed for setting and implementing management tasks exploitation service life of buildings and structures in corrosive environments. It achieved by improving the quality and reliability of primary and secondary protection steel structures considering corrosion level hazards management of process safety within a specified period of Builder-structures service. Originality. The principles of robust design of corrosion protection, taking into account the established reliability and constructive security with combined metal structures under corrosive environments based on the methodology of limit states of structures (taking into account the level of danger of corrosion) were developed. The metering method confirmation of conformity corrosion protection measures for reserving a workable and tasks of the service life composite structures and their protective coatings was used. Practical value. The substantiation methodology of the design solutions and assessment of their conformity upon corrosion risks indicators of construction projects was developed. Technical solutions providing the level reduction of risk emergency situations were realized.